Actinomyces in Blood: Is it Clinically Significant or Insignificant?. (4th October 2017) - Datta, Siddhant; Soliman, Megan; Laguio, Maryrose
Abstract: Background: Actinomyces species are Gram-positive anaerobic organisms associated with a wide range of infections: dental caries, abscesses, intraabdominal and blood stream infections. They colonize human oropharynx, gastrointestinal and urogenital tracts. Traditionally, isolation of actinomyces from any sterile specimen was always considered significant. Over the last few years, there has been a rise in number of reported positive blood cultures. Methods: Our clinical microbiology laboratory database was used to identify positive blood cultures for actinomyces between the period of January 2015 to April 2017. Electronic medical records were reviewed to collect information about patients' demographics, co-morbidities, primary source of infection, treatment received and duration of therapy. Results: A total of 21 cases of positive blood cultures were identified. 13 were females and 8 were males ranging from 22–90 years (65.5 ± 18.8). Only 3 patients were noted to be immunocompromised. The primary source of infection was found in 10 cases: genitourinary (5) was the most common followed by oropharyngeal (2), gastrointestinal (2), and 1 pulmonary. Species were finalized in 8 cases; A.odontolyticus (5), A.meyeri (2) and A.israelli (1). The infectious diseases service was consulted in 7 cases, of which 6 patients received prolonged treatment between 2–12 months with aim to treat disseminated actinomyces infection. Five patients did not receive any antibiotics as the cultures were considered contaminants by the primary provider. The remaining 10 patients received a shorter course between 10 and 21 days targeting conditions like pneumonia, pyelonephritis, and cellulitis. There were three deaths: one patient died after completion of 2 weeks of decided duration of antibiotics; the other two deaths occurred within five days of hospitalization due to unrelated reasons. Conclusion: Actinomyces bacteremia, once rare is now more commonly reported due to modern culture techniques. Not all positive cultures may be meaningful and it can present as transient bacteremia. Better awareness among providers is necessary and involvement of infectious disease service is recommended. If true bacteremia untreated, it can prove fatal. Disclosures: All authors: No reported disclosures.